Fluid ingestion and exercise hyperthermia: Implications for performance, thermoregulation, metabolism and the development of fatigue - Kay, D.; Marino,F. E. (Journal of Sports Sciences, 2000)
The development of fatigue during exercise and the subsequent onset of exhaustion occur earlier in the heat than in cooler environments. The underlying mechanisms responsible for the premature development of fatigue in the heat have yet to be clearly identified. However, the proposed mechanisms include metabolic, cardiovascular and central nervous system perturbations, together with an elevated core temperature. Fluid ingestion is one of three strategies that have been shown to be successful in enhancing the performance of endurance exercise in the heat, with the other interventions being precooling and acclimatization. However, like the development of fatigue in the heat, the mechanisms by which fluid ingestion allows for improved exercise performance remain unclear. We propose that fluid ingestion enhances exercise performance in the heat by increasing the heat storage capacity of the body. We suggest that the thermoregulatory, metabolic and cardiovascular alterations that occur as a result of this increased heat storage capacity contribute to performance enhancement when fluid is ingested during exercise heat stress.